2016
DOI: 10.5468/ogs.2016.59.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Uterine prolapse in a primigravid woman

Abstract: Uterine prolapse during pregnancy is an uncommon condition. It can cause preterm labor, spontaneous abortion, fetal demise, maternal urinary complication, maternal sepsis and death. We report the case of uterine prolapse in a 32-year-old healthy primigravid woman. She had no risk factors associated with uterine prolapse. She was conservatively treated, resulting in a successful vaginal delivery. This report is a very rare case of uterine prolapse in a young healthy primigravid woman, resulting in a successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…(18) In another study stated that there is a small proportion of uterine prolapse cases occurring in nullipara, a rarity which should be studied further. (19) Although the results of Fisher Exact Test analysis of obesity factors showed that there was a significant difference in the incidence of uterine prolapse rate between obese and non-obese patients. However, there is no evidence that obesity affects the degree of uterine prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…(18) In another study stated that there is a small proportion of uterine prolapse cases occurring in nullipara, a rarity which should be studied further. (19) Although the results of Fisher Exact Test analysis of obesity factors showed that there was a significant difference in the incidence of uterine prolapse rate between obese and non-obese patients. However, there is no evidence that obesity affects the degree of uterine prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…According to a case review of pregnancies with uterine prolapse reported by Kana et al [ 7 ], since 1997, vaginal delivery could be performed in only 2 of 16 patients with cervical edema, and none of them was diagnosed with complete uterine prolapse. Jeong et al [ 8 ] reported that, since 2002, only 1 of 14 patients with uterine prolapse was able to be delivered vaginally. These results suggest that this study reports a valuable case of vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Parity contained several components (pregnancy, labor, delivery) that each of them may lead to pelvic relaxation. On that point is an argument about the effect of labor, without vaginal delivery; most of studies suggest that it has a negligible effect on the uterine prolapsed but some data have yielded opposite results [6,7].…”
Section: Discussionmentioning
confidence: 99%